SOSIALISASI PEMBUATAN LAPORAN KEUANGAN KEGIATAN PKK DI DESA PESAREN - Fikrotul Amna; Sintiana Rizki; Umi Kholilah; Ria Anisatus Sholihah; Hendri Hermawan Adinugraha (DPPM Universitas Pelita Bangsa, 2022)
It is hoped that the PKK in Pesaren Village can empower women to participate in the development of Pesaren Village. In practice, the PKK Women's Organization in Pesaren village often faces obstacles in preparing accountability reports in the form of monthly and annual financial reports. Therefore, this community service activity aims to channel knowledge and techniques for making simple financial reports for the PKK in Pesaren village, so that the PKK Women's Organization in Pesaren village can be independent in making their financial reports. The method used is in the form of delivering material on how to prepare financial reports. The results of the activity showed that prior to the implementation of the PKM the PKK Women's Organization in Pesaren village had little mastery about simple financial reports, but after the implementation of the activities it was discovered that the PKK Women's Organization in Pesaren village was quite skilled and able to make financial reports PKK. PKM activities indirectly play a positive role in increasing participant knowledge and participant skills in making PKK financial reports.